Development of production sequencing software for industry - Mohd Zaini, Jamak (2008)
The aim of this project is to develop a production sequencing software for specific company. Research has started with the trailing of a specific area in their production process that undergo problem in term of sequencing. Thus, in the first phase, all the problem sources and correlation in that area have been identified to overcome it using the sequencing element. Next, the problems that have been identified were solved through the development of software to provide an organized computerized sequencing system. The software has been developed by Visual Basic .NET that filled all the problem solving criteria and was simulated so that it is suitable with the environment of research area. At the final of the project, the production sequencing software have been developed successfully and accepted by company to improve the sequencing in research area.